Penguatan Kapasitas Masyarakat Pesisir dalam Penanganan Pascapanen Rumput Laut Kappaphycus alvarezii - *Faiza A. Dali; Rita Marsuci Harmain; Anton Kaharu (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This community service activity was conducted in Tolango Village, North Gorontalo Regency, a coastal area where Kappaphycus alvarezii seaweed cultivation is practiced. The activity aimed to strengthen community knowledge and practices related to seaweed post-harvest handling. The program employed a participatory, group-based learning approach through counseling, training, and technical assistance that actively involved community partners at each stage. Assistance materials covering washing, drying, removal of impurities and salt, packaging, transportation, and storage of harvested seaweed were delivered as part of the activity. This program resulted in a more structured understanding of basic principles of seaweed post-harvest handling as part of orderly and sustainable dried seaweed management at the coastal community level.